Implementasi Kurikulum 2013 Pada Pembelajaran - Fatmawaty Fatmawaty (Jambura Journal of Educational Management, 2023)
This article discusses how the process of implementing the 2013 Curriculum on Indonesian Learning at MI Ikhlasiyah Palembang, with the background that Indonesian learning at the Madrsah Ibtidaiyah level must be carried out by looking at the regulations that have been set by the government, namely K13. The type of research used is qualitative with a descriptive approach. Data collection methods are through interviews, observations and documentation, while data analysis techniques start from data reduction, presentation and verification of data. To see the validity of the data, it is done using data triangulation. The results obtained are the implementation of the 2013 Curriculum on Learning Indonesian has been carried out properly by looking at the guidelines that have been set by the government. Then from the aspect of learning kenten that the teacher has conditioned learning that is interactive, inspiring, fun, challenging, motivate learners to participate actively, as well as provide sufficient space for initiative, creativity, and independence according to the talents, interests, and physical and psychological development of students. In the learning process, the basic competencies of Indonesian subjects are divided into 3 domains and have been carried out covering the realm of attitudes, the realm of knowledge, and the realm of skills.